The Dimensions of Experiential Learning in the Management of Activity Load - Castellaneta, Francesco; Zollo, Maurizio (Organization Science, 2015)
Drawing on the attention-based view of the firm and the experiential learning literature, this paper develops and tests a theory on how firms learn to cope with the strains of activity load. We first empirically test the impact of activity load on the performance of a focal activity. We then study how this relationship is moderated by four dimensions of experiential learning: stock, homogeneity, pacing, and past success. We test our hypotheses on a proprietary database of 6,913 investments by 248 private equity firms in 77 countries between 1973 and 2008. We find that heavier activity loads exact a smaller toll on performance when firms have larger and more homogeneous stocks of prior experience. However, when firms’ prior experience is more rapidly paced or successful, the toll of heavier activity loads on performance grows. Taken together, these four dimensions of experiential learning provide an initial theoretical basis for the development of a capability that we term attention modulation capability.